Impact of age in the production of European Portuguese vowels - Albuquerque, L. (2022)
The elderly population is quickly increasing in the developed countries. However, in European Portuguese (EP) no studies have examined the impact of age-related structural changes in speech acoustics. The purpose of this paper is to analyse the effect of age ([60-70], [71-80] and [81-90]), gender and type of vowel in the acoustic characteristics (fundamental frequency (F0), first formant (F1), second formant (F2) and duration) of the EP vowels. A sample of 78 speakers was selected from the database of elderly speech collected by Microsoft Language Development Center (MLDC) within the Living Usability Lab (LUL) project. It was observed that duration is the only parameter that significantly changes with ageing, being the highest value found in the [81-90] group. Moreover, F0 decreases in females and increases in males with ageing. In general, F1 and F2 decreases with ageing, mainly in females. Comparing the data obtained with the results of previous studies with adult speakers, a trend towards the centralization of vowels with ageing is observed. This investigation is the starting point for a broader study which will allow to analyse the changes in vowels acoustics from childhood to old age in EP.